A Study Of Religion In Analytic Philosophy With Special Reference To Bertrand Russell (Journal of Namibian Studies : History Politics Culture, 2023)
Russell specially discusses religion in his well known book, ‘Why I am not a Christian’. Russell’s writings about religion are expressed in the following quote as- “We want to stand upon our own feet and look fair and square at the world...........conquer the world by intelligence, and not merely by being slavishly subdued by the terror that comes for it.”